Association of Tumor Necrosis Factor-Alpha Gene Polymorphisms With Juvenile Systemic Lupus Erythematosus Nephritis in a Cohort of Egyptian Patients (Iranian Journal of Kidney Diseases, 2011)
Introduction. The production of tumor necrosis factor (TNF)-alpha has been deeply deregulated in systemic lupus erythematosus. We evaluated the association of -863C>A and -1031T>C polymorphisms of the TNF gene with susceptibility to and clinical manifestations of juvenile systemic lupus erythematosus.Materials and Methods. This study was performed on 70 juvenile patients with systemic lupus erythematosus (mean age, 13.0 ± 4.2 years). Ninety age- and sex-matched children served as a controls. All participants were genotyped for the TNF -863C>A and -1031T>C polymorphisms by polymerase chain reaction-restriction fragment length polymorphism method. Analysis of serum TNF-alpha was done by solid-phase sandwich enzyme immunoassay.Results. The mean serum TNF-alpha was significantly higher in the SLE patients compared to controls (P < .001). Regarding all participants, the mean serum TNF-alpha was significantly higher in children with -863AA genotype compared to carriers of -863C allele (P < .001). The TNF -863AA genotype frequencies were significantly higher in the patients group compared with the controls (P = .005) and were associated with increased risk for SLE development (odds ratio, 4.05; 95% confidence interval, 1.38 to 13.13; P = .005). The -863AA variant was associated with nephritis (P < .001) and Raynaud phenomenon (P = .001).Conclusions. The -863A allele of the TNF gene can be used as a genetic marker for SLE susceptibility and was associated with high TNF-alpha production, Raynaud phenomenon, and nephritis in juvenile SLE Egyptian patients.